Implementation Policy Service Administration Integrated Sub-district (PATEN) in Sape District, Sape Regency Bima - Saputra, Farhan Adi; Madani, Muhlis; Usman, Jaelan; Mappasere, Fatmawati A.; Mustari, Nuryanti; Parawu, Hafiz Elfiansya; Razak, Andi Rosdianti (Ilomata International Journal of Management, 2025)
The implementation of public service reforms through the Integrated Administrative Services (PATEN) policy aims to simplify administrative processes and enhance service quality at the sub-district level. In Sape Sub-district, Bima Regency, the policy has been adopted to provide fast and integrated services. However, challenges such as poor communication, limited resources, and overlapping bureaucracy hinder its effectiveness. This study evaluates the PATEN policy's implementation in Sape Sub-district, focusing on communication, resources, personnel placement, and bureaucratic structure. The research uses a qualitative descriptive approach with data collected through interviews, observations, and documentation. The findings aim to identify challenges and provide recommendations to improve the efficiency and quality of public services at the sub-district level.